Correlation of medial longitudinal arch height with postural stability, sensory integration, balance and fall risk among healthy young adults - Gul, Sameera; Hafiza Noor ul Huda; Raza, Misha; Muhammad Osama (Journal of the Pakistan Medical Association, 2023)
A cross-sectional analytical study was conducted on 165 healthy young adults. Individuals with pes rectus and pes planus to correlate the medial longitudinal arch height with postural stability, sensory integration and balance and fall risks. Persons with pes cavus, congenital foot anomalies other than pes planus, leg length discrepancies, recent history of trauma, lower limb amputations, history of serious foot injury, ligamentous laxity, or an active inflammatory disorder were excluded. Outcome measurements included normalised truncated navicular height (NTNH), Chippaux Smirak index (CSI), single leg athletic stability (ASLS) index, fall risk (FR) index, postural stability (PS), clinical test of sensory integration of balance (CTSIB), and balance error scoring system (BESS). Spearman correlation and Mann Whitney U test were used for data analysis. —Continue